Pengaruh Pajak Hotel, Pajak Rumah Makan dan Retribusi Objek Wisata Terhadap Pendapatan Asli Daerah di Kabupaten Nabire Tahun 2011 - 2020 - Ferderika Yunike Kegou; Marcus Maspaitella; Ketysia Imelda Tewernussa (Lensa Ekonomi, 2022)
This study aims to determine the effect of hotel taxes, restaurant taxes and tourist object levies on local revenue in Nabire Regency in 2011-2022. The method of analysis used is the method of multiple linear regression analysis, classical assumptions with secondary data. Data analysis was carried out using the SPSS version 21 analysis tool. The results of the study show that Hotel Taxes, Restaurant Taxes and Tourist Object Levies show their influence on Regional Original Income. This is based on the results of the significance of hotel taxes, restaurant taxes and tourist attraction levies, each of which is 0.020, 0.039, 0.042 which is smaller with a significance value of 5%.